Primary Hydatid Cyst of the Small Intestine: A Rare Case Report and Brief Review of the Literature - (:unkn) unknown (CUREUS INC, 2016)
Hydatid disease is an endemic disease especially in underdeveloped and developing countries affecting mostly the liver and lungs. The hydatid cysts located in other sites are mostly due to rupture of primary liver or splenic cysts. We present a primary small intestine hydatid cyst resected laparoscopically with the affected intestinal segment. As far as we know, this is the first report of a primary small intestine hydatid disease in the literature.
Keywords: hydatid disease; small intestine; surgery; laparoscopy; ECHINOCOCCOSIS